Anti-inflammatory effect of torilidis fructus ethanol extract through inhibition of Src - Gyubyung Park; Eunji Kim; Young-Jin Son; Deok Hyo Yoon; Gi-Ho Sung; Adithan Aravinthan; Yung Chul Park; Jong-Hoon Kim; Jae Youl Cho (Taylor & Francis Group, 2017)
Context: Torilidis fructus, fruits of Torilis japonica Decadolle (Umbelliferae), is a medicinal herb traditionally used as a pesticide, an astrictive, or a medicine for various inflammatory diseases. Objectives: Due to the lack of pharmacological studies on this herbal medicine, we explored the inhibitory activity of torilidis fructus on the macrophage-mediated inflammatory response using its ethanol extract (Tf-EE). Material and methods: The Griess assay and prostaglandin (PGE2) ELISA assay were conducted with Tf-EE (0-75 µg/mL) and LPS (1 µg/mL) treated RAW264.7 cells in cultured media. Tf-EE pretreated RAW264.7 cells were incubated with LPS for 6 h and semi-quantitative PCR was performed. Reporter gene assays, overexpression of target enzymes and immunoblotting were performed on macrophages to determine the molecular targets of Tf-EE. Results: Tf-EE markedly suppressed the inflammatory response of macrophages, such as lipopolysaccharide (LPS)-induced nitric oxide (NO) and PGE2 production with IC50 values of 35.66 and 62.47 µg/mL, respectively. It was also found that Tf-EE reduced the expression of inducible NO synthase (iNOS) and cyclooxygenase (COX)-2 by 80%. Nuclear translocation and activation of nuclear factor (NF)-κB (p65 and p50) were declined by 60% and 30% respectively, and their regulatory events including the phosphorylation of AKT, IκBα, Src, and the formation of complexes between Src and p-p85 were also recognized to be diminished. Conclusions: The signalling events managed by Src and p85 complex seemed to be critically involved in Tf-EE-mediated anti-inflammatory response. This might suggest that Tf-EE exhibited anti-inflammatory effects through Src-targeted inhibition of NF-κB.